Positive electrode lithium supplementing material and preparation method and application thereof

By forming a shell with a gradient distribution of fluorine element on the positive electrode lithium supplement material, the problem of poor structural stability of the existing positive electrode lithium supplement material is solved, and the cycle stability and cycling performance of the battery are significantly improved.

CN119563243AActive Publication Date: 2025-03-04NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202480003006.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-03-04
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing positive electrode lithium supplement material has poor structural stability during the circulation process, resulting in fast battery capacity decay and poor circulation performance.

Method used

A material including a positive electrode lithium supplement matrix material and a fluorine element gradient distribution shell layer is used. The chemical formula of the shell layer is AaZrFb, wherein 0

Benefits of technology

By forming a shell with gradually increasing density, the structural stability of the positive electrode lithium supplement material is enhanced and the cycle stability and circulation performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119563243A_ABST
    Figure CN119563243A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a positive electrode lithium supplementing material and a preparation method and application thereof, and aims to improve the structural stability of the positive electrode lithium supplementing material and the cycle performance of the battery. The positive electrode lithium supplementing material comprises a positive electrode lithium supplementing base material and a shell layer existing on at least part of the surface of the positive electrode lithium supplementing base material, the shell layer comprises a fluorine element, and the content of the fluorine element in the shell layer is in a trend of increasing along the direction from the positive electrode lithium supplementing matrix material to the shell layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode lithium supplement material and a preparation method and application thereof. Background Art

[0002] In the field of battery manufacturing technology, the quality of positive electrode active materials directly affects the performance of the battery, such as energy density, power density, cycle life, etc. However, during the battery charging and discharging process, a solid electrolyte interface film will form on the surface of the positive electrode active material. This process will consume part of the active lithium in the positive electrode active material and will not be restored, which will cause problems such as low battery capacity, low initial coulomb efficiency, and poor cycle life. The use of positive electrode lithium supplement materials can effectively reduce the irreversible loss of active lithium, and at the same time, the structure of the positive electrode active material can be restored in time, thereby ensuring the normal performance of the material's electrical properties.

[0003] The existing commonly used positive electrode lithium supplement materials often have the problem of poor structural stability during the cycle process, which makes the battery capacity decay quickly and the cycle performance is poor. Therefore, it is urgent to develop a positive electrode lithium supplement material with high structural stability to improve the cycle performance of the battery. Summary of the invention

[0004] The present application discloses a positive electrode lithium supplement material and a preparation method and application thereof, in order to solve the problems of poor structural stability and poor battery cycle performance of existing positive electrode lithium supplement materials.

[0005] In order to achieve the above objectives, this application provides the following technical solutions:

[0006] In a first aspect, the present application provides a positive electrode lithium replenishing material, comprising a positive electrode lithium replenishing matrix material and a shell layer present on at least a portion of the surface of the positive electrode lithium replenishing matrix material; the shell layer comprises fluorine element, and the content of fluorine element in the shell layer tends to increase along the direction from the positive electrode lithium replenishing matrix material to the shell layer.

[0007] Furthermore, the chemical formula of the shell is A a ZF b , wherein 0<a≤2, 4≤b≤6, A is selected from at least one of K, Na, and NH4;

[0008] And / or, the chemical formula of the positive electrode lithium supplement matrix material is Li x M y O z , wherein 0<x≤4, 0<y≤2, 0<z≤4, and M is selected from at least one of C, Ni, Co, Mn, and Fe.

[0009] Further, the shell layer includes a first shell layer existing on the surface of the positive electrode lithium supplementing matrix material, a second shell layer existing on a side of the first shell layer away from the positive electrode lithium supplementing matrix material, and a third shell layer existing on a side of the second shell layer away from the positive electrode lithium supplementing matrix material;

[0010] The content of fluorine in the first shell layer is less than that in the second shell layer, and the content of fluorine in the second shell layer is less than that in the third shell layer.

[0011] Further, the thickness of the first shell layer is 0.05 μm-0.6 μm; the thickness of the second shell layer is 0.3 μm-0.75 μm; the thickness of the third shell layer is 0.2 μm-1 μm;

[0012] And / or, the mass percentage of fluorine element in the first shell layer to the positive electrode lithium replenishing material is 0.01%-1.5%; the mass percentage of fluorine element in the second shell layer to the positive electrode lithium replenishing material is 1%-3%; the mass percentage of fluorine element in the third shell layer to the positive electrode lithium replenishing material is 3%-5%.

[0013] Furthermore, the D50 of the positive electrode lithium supplement matrix material is 8 μm-10 μm; the total thickness d of the shell layer is 1 μm-2.1 μm;

[0014] And / or, after X-ray diffraction analysis, the half-peak width FWHM (003) of the diffraction peak corresponding to the (003) crystal plane in the X-ray diffraction pattern of the positive electrode lithium supplement material is 0.25°-0.42°; wherein, FWHM (003) = 0.0027d 2 +0.13d+0.13, d is the total thickness of the shell;

[0015] And / or, the proportion of the area of ​​the portion of the surface of the positive electrode lithium-replenishing matrix material where the shell layer does not exist to the total surface area of ​​the positive electrode lithium-replenishing matrix material is less than or equal to 5%.

[0016] Furthermore, in the differential capacitance curve of the battery prepared by the positive electrode lithium supplement material for 0-200 cycles, in the range of 4.1V-4.3V, the fluctuation range of the phase transition peak position I1 is 0%-2%; in the range of 3.4V-3.7V, the fluctuation range of the phase transition peak position I2 is 0%-5%.

[0017] In a second aspect, the present application provides a method for preparing the positive electrode lithium supplement material of the first aspect, comprising the following steps:

[0018] 1) sintering the raw material system including the lithium source and the M source at 300° C.-500° C. in an inert gas atmosphere for 8 h-16 h to obtain a first intermediate;

[0019] 2) performing secondary sintering on the first intermediate at 600° C.-800° C. in an inert gas atmosphere for 8 h-16 h to obtain a second intermediate;

[0020] 3) allowing a redox medium to be deposited once on the surface of the second intermediate to obtain a third intermediate;

[0021] 4) allowing the redox mediator to be deposited secondary on the surface of the third intermediate to obtain a fourth intermediate;

[0022] 5) allowing the redox medium to be deposited three times on the surface of the fourth intermediate to obtain the positive electrode lithium supplement material.

[0023] Further, the temperature of the primary deposition is 400-450° C., the deposition rate is 0.01-0.02 μm / min, and the deposition time is 2.5-30 min;

[0024] And / or, the secondary deposition temperature is 350-400° C., the deposition rate is 0.02-0.03 μm / min, and the deposition time is 10-25 min;

[0025] And / or, the temperature of the three depositions is 300-350° C., the deposition rate is 0.03-0.035 μm / min, and the deposition time is 6-28 min.

[0026] In a third aspect, the present application provides a positive electrode sheet, comprising the positive electrode lithium replenishing material of the first aspect and the positive electrode lithium replenishing material prepared by the preparation method of the second aspect.

[0027] Furthermore, the positive electrode sheet includes a positive electrode current collector, a positive electrode active material layer present on the surface of the positive electrode current collector, and a positive electrode lithium replenishing layer present on a side of the positive electrode active material layer away from the positive electrode current collector.

[0028] In a fourth aspect, the present application provides a battery, comprising the positive electrode sheet of the third aspect.

[0029] The technical solution of this application produces the following beneficial effects:

[0030] The positive electrode lithium replenishing material provided in the present application can replenish lithium for the battery and make up for the loss of lithium ion concentration caused by the lithium ion battery during the cycle process. In the present application, the fluorine content in the shell layer of the positive electrode lithium replenishing material tends to increase along the direction from the positive electrode lithium replenishing matrix material to the shell layer, and a shell layer with gradually increasing density can be formed, which effectively enhances the structural stability of the positive electrode lithium replenishing material, thereby improving the cycle stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1This is a cross-sectional SEM image of the positive electrode lithium supplement material prepared in Example 1 of the present application;

[0032] Figure 2 This is a surface SEM image of the positive electrode lithium supplement material prepared in Example 1 of the present application;

[0033] Figure 3 A graph showing the change in the fluorine content in the positive electrode lithium supplement material prepared in Example 1 of the present application along the distance from the positive electrode lithium supplement matrix material to the shell layer;

[0034] Figure 4 A schematic diagram of the structure of a positive electrode sheet provided in this application. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of this application clearer, this application will be further described in detail below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0036] The application scenarios described in the embodiments of the present application are intended to more clearly illustrate the technical solutions of the embodiments of the present application, and do not constitute a limitation on the technical solutions provided by the embodiments of the present application. It is known to those skilled in the art that with the emergence of new application scenarios, the technical solutions provided by the embodiments of the present application are also applicable to similar technical problems. In the description of the present application, unless otherwise specified, the meaning of "multiple" is two or more.

[0037] In a first aspect, the present application provides a positive electrode lithium replenishing material, comprising a positive electrode lithium replenishing matrix material and a shell layer present on at least a portion of the surface of the positive electrode lithium replenishing matrix material; the shell layer comprises fluorine element, and the content of fluorine element in the shell layer tends to increase along the direction from the positive electrode lithium replenishing matrix material to the shell layer.

[0038] Specifically, the shell layer can be coated on the surface of the positive electrode lithium supplement matrix material, and the content of the fluorine element in the shell layer increases along the direction of the positive electrode lithium supplement matrix material to the shell layer, that is, along the direction of the positive electrode lithium supplement matrix material to the shell layer, a shell layer with gradually increasing density is formed, and the shell layer can be a redox medium layer. The gradual increase in density strengthens the binding of the redox medium and the positive electrode lithium supplement matrix material, which is conducive to improving the transmission of charge, that is, the diffusion process of ions. The gradually increasing fluorine element content can reduce the ion diffusion impedance and effectively optimize the ion diffusion. The gradient distribution makes the ions diffuse more smoothly inside the positive electrode lithium supplement material, reducing the ion diffusion resistance. At the same time, the outer high-density shell layer can increase the structural stability of the positive electrode lithium supplement material, reduce the degradation of the positive electrode lithium supplement material structure and the increase of the interface impedance during the charge and discharge process, thereby extending the cycle life of the battery. In addition, the redox medium can also spontaneously react with the dead lithium on the surface of the negative electrode, and the reaction is a reversible reaction, which can effectively extend the cycle life of the battery. Specifically, during the charging process, the oxidized redox medium can spontaneously react with the dead lithium on the surface of the metallic lithium negative electrode to become a reduced redox medium, which then diffuses to the positive electrode side and loses electrons and is oxidized again to an oxidized redox medium; this can effectively reduce the impact of dead lithium on the battery cycle performance without affecting the performance of the positive electrode lithium supplement matrix material.

[0039] The fluorine content in the present application can be measured by X-ray energy dispersive spectroscopy (EDS) line scanning.

[0040] The positive electrode lithium replenishing material of the present application can replenish lithium for the battery and make up for the loss of lithium ion concentration caused by the lithium ion battery during the cycle process. In addition, the fluorine content in the shell layer of the positive electrode lithium replenishing material in the present application tends to increase along the direction from the positive electrode lithium replenishing matrix material to the shell layer, and a shell layer with gradually increasing density can be formed, which effectively enhances the structural stability of the positive electrode lithium replenishing material, thereby improving the cycle stability of the battery.

[0041] Specifically, the chemical formula of the shell is A a ZF b , wherein 0<a≤2, 4≤b≤6, and A is selected from at least one of K, Na, and NH4.

[0042] In some embodiments, the chemical formula of the positive electrode lithium supplement matrix material is Li x M y O z , wherein 0<x≤4, 0<y≤2, 0<z≤4, and M is selected from at least one of C, Ni, Co, Mn, and Fe. The positive electrode lithium supplement matrix material is used to facilitate the lithium supplement function, and the redox medium is coated on its surface to improve its stability, thereby improving the cycle performance of the battery.

[0043] For example, A aZF b In the formula (a), a can be 0.1, 0.5, 1, 1.5, 2 or any two thereof, and b can be 4, 4.5, 5, 5.5, 6 or any two thereof. x M y O z , x can be 0.1, 0.5, 1, 1.5, 2, 3, 4 or a range consisting of any two thereof, y can be 0.1, 0.5, 1, 1.5, 2 or a range consisting of any two thereof, and z can be 0.1, 0.5, 1, 1.5, 2, 3, 4 or a range consisting of any two thereof.

[0044] The shell layer in this application is fluorozirconate, which, as a redox medium, can adjust the kinetics of the reaction by changing the electron density on the electrode surface or changing the chemical environment on the electrode surface. This adjustment helps to achieve more efficient electron transfer and more uniform electrochemical reactions, thereby improving the energy density and rate performance of the battery. In addition, the fluorozirconate shell layer can form a stable protective film on the surface of the positive electrode lithium replenishment matrix material, reduce the direct contact between the electrolyte and the positive electrode lithium replenishment matrix material, and reduce the probability of side reactions, thereby improving the structural stability of the positive electrode lithium replenishment material, and then improving the cycle performance of the battery.

[0045] The use of the above-mentioned positive electrode lithium-supplementing matrix material is conducive to the lithium-supplementing function. At the same time, coating the surface of the positive electrode with fluorozirconate can improve its structural stability, thereby improving the cycle performance of the battery.

[0046] In some embodiments of the present application, the shell layer includes a first shell layer present on the surface of the positive electrode lithium-supplementing matrix material, a second shell layer present on the side of the first shell layer away from the positive electrode lithium-supplementing matrix material, and a third shell layer present on the side of the second shell layer away from the positive electrode lithium-supplementing matrix material.

[0047] The content of fluorine in the first shell layer is less than that in the second shell layer, and the content of fluorine in the second shell layer is less than that in the third shell layer.

[0048] In the present application, the shell layer includes a first shell layer, a second shell layer and a third shell layer. Specifically, the first shell layer exists on the surface of the positive electrode lithium supplement matrix material, which may be a partial surface or the entire surface; the second shell layer exists on the side of the first shell layer away from the positive electrode lithium supplement matrix material, which may be a partial surface or the entire surface; the third shell layer exists on the side of the second shell layer away from the positive electrode lithium supplement matrix material, which may be a partial surface or the entire surface. The first shell layer can provide preliminary protection for the positive electrode lithium supplement matrix material, the second shell layer further enhances the protection of the positive electrode lithium supplement matrix material, and the third shell layer provides the strongest protection. This gradient structure can effectively prevent the electrolyte from corroding the positive electrode lithium supplement matrix material and significantly improve the structural stability of the positive electrode lithium supplement material. And the gradient shell layer design can alleviate the stress concentration caused by the stress difference between materials of different levels, reduce the mechanical stress and lattice distortion of the material during the charge and discharge process, thereby improving the mechanical strength and structural stability of the material.

[0049] The content of fluorine in the first shell of the present application is less than the content of fluorine in the second shell, and the content of fluorine in the second shell is less than the content of fluorine in the third shell. This layer-by-layer increase in fluorine content forms a gradient protection structure. The lower fluorine content in the first shell helps to maintain good electronic and ionic conductivity and ensure the efficient conduction of electrochemical reactions. As the fluorine content increases, the second and third shells can provide stronger chemical stability and protection, thereby improving the structural stability of the positive electrode lithium supplement material. In addition, the high content of fluorine in the third shell can form a stable protective film, reduce the side reactions of the electrolyte and the positive electrode lithium supplement material, reduce the decomposition of the electrolyte and the generation of by-products on the electrode surface, thereby improving the cycle life of the battery.

[0050] In some embodiments of the present application, the thickness of the first shell layer is 0.05 μm-0.6 μm; the thickness of the second shell layer is 0.3 μm-0.75 μm; and the thickness of the third shell layer is 0.2 μm-1 μm.

[0051] In some embodiments, the mass percentage of fluorine element in the first shell layer to the positive electrode lithium replenishing material is 0.01%-1.5%; the mass percentage of fluorine element in the second shell layer to the positive electrode lithium replenishing material is 1%-3%; the mass percentage of fluorine element in the third shell layer to the positive electrode lithium replenishing material is 3%-5%.

[0052] Exemplarily, the thickness of the first shell layer can be 0.05μm, 0.1μm, 0.15μm, 0.2μm, 0.25μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm or a range consisting of any two thereof, the thickness of the second shell layer can be 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.75μm or a range consisting of any two thereof, and the thickness of the third shell layer can be 0.2μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1μm or a range consisting of any two thereof. The mass percentage of fluorine element in the first shell layer to the positive electrode lithium replenishing material can be 0.01%, 0.05%, 0.07%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.5% or a range consisting of any two thereof; the mass percentage of fluorine element in the second shell layer to the positive electrode lithium replenishing material can be 1%, 1.5%, 2%, 2.5%, 3% or a range consisting of any two thereof; the mass percentage of fluorine element in the third shell layer to the positive electrode lithium replenishing material can be 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two thereof.

[0053] In the present application, the thickness of the first shell layer, the second shell layer and the third shell layer can be obtained by measuring the content of fluorine in each shell layer through EDS line scanning. Specifically, after the first shell layer is deposited on the positive electrode lithium supplementation matrix material, an EDS line scan is performed, and the thickness of the first shell layer is obtained by testing the thickness of the area where the mass percentage of fluorine is greater than 0.5%; after the second shell layer is deposited on the positive electrode lithium supplementation matrix material, an EDS line scan is performed, and the first thickness is obtained by testing the thickness of the area where the mass percentage of fluorine is greater than 1.5%, and the thickness of the second shell layer is obtained by subtracting the first thickness from the first shell layer thickness; after the third shell layer is deposited on the positive electrode lithium supplementation matrix material, an EDS line scan is performed, and the second thickness is obtained by testing the thickness of the area where the mass percentage of fluorine is greater than 3%, and the thickness of the third shell layer is obtained by subtracting the first thickness from the second thickness.

[0054] In the present application, the thickness of the first shell layer, the second shell layer and the third shell layer and the mass percentage of the fluorine element in the first shell layer, the second shell layer and the third shell layer in the positive electrode lithium supplement material are within the above range, which can further improve the structural stability of the positive electrode lithium supplement material, reduce the increase in interface impedance during the charge and discharge process, and thus improve the cycle performance of the battery.

[0055] In some embodiments of the present application, the D50 of the positive electrode lithium-supplementing matrix material is 8 μm-10 μm; and the total thickness d of the shell layer is 1 μm-2.1 μm.

[0056] In some embodiments, after X-ray diffraction analysis, the half-peak width FWHM (003) of the diffraction peak corresponding to the (003) crystal plane in the X-ray diffraction pattern of the positive electrode lithium supplement material is 0.25°-0.42°; wherein, FWHM (003) = 0.0027d 2 +0.13d+0.13, d is the total thickness of the shell layer.

[0057] In some embodiments, the proportion of the area of ​​the portion of the surface of the positive electrode lithium-supplementing matrix material where the shell layer does not exist is less than or equal to 5% of the total surface area of ​​the positive electrode lithium-supplementing matrix material.

[0058] Exemplarily, the D50 of the positive electrode lithium supplement matrix material can be 8μm, 8.5μm, 9μm, 9.5μm, 10μm or any two thereof, and the total thickness d of the shell layer can be 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.1μm or any two thereof. The half-peak width FWHM (003) of the diffraction peak corresponding to the (003) crystal plane in the X-ray diffraction pattern of the positive electrode lithium supplement material can be 0.25°, 0.3°, 0.32°, 0.35°, 0.38°, 0.4°, 0.42° or any two thereof. The area of ​​the portion of the surface of the positive electrode lithium supplement matrix material where there is no shell layer accounts for a proportion of the total surface area of ​​the positive electrode lithium supplement matrix material, which can be 1%, 2%, 3%, 4%, 5% or any two thereof.

[0059] In the present application, the D50 of the positive electrode lithium supplement matrix material is within the above range, which can provide a good specific surface area, help improve the electrochemical reaction activity and efficiency, and can also balance the conductivity and ion mobility, ensure that the positive electrode lithium supplement material has good rate performance and energy density, and also help improve the mechanical strength and structural stability of the positive electrode lithium supplement material, and reduce the pulverization and breakage during the charge and discharge process. The total thickness d of the shell layer is within the above range, which can provide effective protection for the positive electrode lithium supplement matrix material, prevent the electrolyte from corroding the positive electrode lithium supplement matrix material, reduce the occurrence of side reactions, and also help improve the structural stability of the positive electrode lithium supplement material, reduce the increase of interface impedance during the charge and discharge cycle, thereby improving the cycle performance and rate performance of the battery.

[0060] In the present application, the total thickness of the shell layer closely affects the uniformity of the lithium ion deintercalation channel. The total thickness of the shell layer changes with the gradient, which can effectively regulate the uniformity of the lithium ion deintercalation channel, and then regulate the uniformity of charging and discharging. A moderate total thickness of the shell layer can reduce the polarization phenomenon of the electrode material during the charging and discharging process, reduce the internal resistance of the battery, and thus improve the energy density and rate performance of the battery. An excessively thick surface coating will inhibit the reverse deintercalation of lithium ions.

[0061] In the present application, the area of ​​the portion of the surface of the positive electrode lithium-replenishing matrix material where no shell exists accounts for less than or equal to 5% of the total surface area of ​​the positive electrode lithium-replenishing matrix material, which means that the shell coverage is relatively high, and can provide comprehensive protection for the positive electrode lithium-replenishing matrix material, so that the positive electrode lithium-replenishing material maintains structural stability during the charging and discharging process, prevents direct contact between the electrolyte and the positive electrode lithium-replenishing matrix material, reduces the occurrence of side reactions, reduces the increase in interfacial impedance during the charging and discharging process, and improves the battery's cycle performance and rate performance.

[0062] In some embodiments of the present application, in the differential capacitance curve of the battery cycle 0-200 cycles prepared by the positive electrode lithium supplement material, in the range of 4.1V-4.3V, the fluctuation range of the phase transition peak position I1 is 0%-2%; in the range of 3.4V-3.7V, the fluctuation range of the phase transition peak position I2 is 0%-5%.

[0063] Specifically, the preparation method of the battery in the present application may include the following steps: at 25°C and normal pressure (0.1MPa), the positive electrode active material NCM622, the conductive agent Super P, and the binder polyvinylidene fluoride (PVDF) are stirred and mixed in an N-methylpyrrolidone solvent in a mass ratio of 8:1:1 to obtain a positive electrode slurry with a solid content of 70%. The positive electrode lithium replenishing material, conductive carbon black, and binder polyvinylidene fluoride (PVDF) of the present application are stirred and mixed in an N-methylpyrrolidone solvent in a mass ratio of 4:2:2 to obtain a positive electrode lithium replenishing slurry with a solid content of 20%. The positive electrode lithium replenishing slurry is coated on the current collector Al foil by transfer coating, and the positive electrode slurry loading surface density is controlled at 13mg / cm 2 -15mg / cm 2 The coating speed is 1mL / min. After the positive electrode slurry is pre-coated for 400mm, the slurry nozzle is turned on to spray the positive electrode lithium supplement slurry. The spraying pressure is 0.5MPa and the spraying speed is 10mL / min. After coating, the positive electrode is dried in an oven at 110℃-130℃. The negative electrode is made of graphite, and the diaphragm polypropylene PP and electrolyte (the electrolyte composition is 1mol / L LiPF6, and the volume ratio of EC / DMC / DEC is 1:1:1) form a full battery.

[0064] At 25°C, charge at a constant current of 1C to 4.35V, charge at a constant voltage of 4.35V to a current rate of 0.5C, and then discharge at a discharge rate of 1C to 3.0V. Repeat 200 charge and discharge cycles. Process the collected data, calculate the voltage change (dV) and charge change (dQ) in each cycle, and use dQ / dV (the ratio of charge change to voltage change) as the ordinate and voltage or capacity as the abscissa to obtain the standard differential capacitance (dQ / dV) curve.

[0065] Exemplarily, the fluctuation range of the phase transition peak position I1 can be 0%, 0.5%, 1%, 1.5%, 2% or a range consisting of any two of them, and the fluctuation range of the phase transition peak position I2 can be 0%, 1%, 2%, 3%, 4%, 5% or a range consisting of any two of them.

[0066] In the present application, the fluctuation range of the phase transition peak position I1 in the interval of 4.1V-4.3V and the phase transition peak position I2 in the interval of 3.4V-3.7V are within the above range, indicating that the surface battery has stable phase change behavior during the cycle, and the positive electrode lithium supplement material maintains good structural stability and electrochemical stability during the charging and discharging process; the fluctuation range of the phase transition peak position is small, indicating that the battery has a lower capacity attenuation during the cycle, and can maintain a higher capacity and energy density during long-term use, thereby extending the cycle life of the battery.

[0067] In a second aspect, the present application provides a method for preparing the positive electrode lithium supplement material of the first aspect, comprising the following steps:

[0068] 1) sintering the raw material system including the lithium source and the M source at 300° C.-500° C. in an inert gas atmosphere for 8 h-16 h to obtain a first intermediate;

[0069] 2) performing secondary sintering on the first intermediate at 600° C.-800° C. in an inert gas atmosphere for 8 h-16 h to obtain a second intermediate;

[0070] 3) allowing a redox medium to be deposited once on the surface of the second intermediate to obtain a third intermediate;

[0071] 4) allowing the redox mediator to be deposited secondary on the surface of the third intermediate to obtain a fourth intermediate;

[0072] 5) allowing the redox medium to be deposited three times on the surface of the fourth intermediate to obtain the positive electrode lithium supplement material.

[0073] In the present application, three deposition processes are performed to finally prepare the positive electrode lithium supplement material of the first aspect of the present application.

[0074] Specifically, in step 1), a lithium source, such as lithium hydroxide, and an M source can be put into a high-speed mixer in a certain proportion and mixed for 3h-5h to obtain sample A1; then sample A1 is placed in a ball mill and ball-milled at a speed of 500rpm to obtain sample A2; sample A2 is sintered once for 8h-16h in an inert gas atmosphere to obtain a first intermediate. Wherein, the M source is a compound of at least one element of C, Ni, Co, Mn, and Fe. The temperature of the primary sintering can be 300°C, 350°C, 400°C, 450°C, 500°C or a range consisting of any two thereof, and the time of the primary sintering can be 8h, 10h, 12h, 14h, 16h or a range consisting of any two thereof.

[0075] In step 2), the first intermediate is cooled and then ball-milled again, and then the crushed first intermediate is subjected to secondary sintering for 8h-16h at 600°C-800°C in an inert gas atmosphere to obtain a second intermediate. The secondary sintering temperature may be 600°C, 650°C, 700°C, 750°C, 800°C or any two thereof, and the secondary sintering time may be 8h, 10h, 12h, 14h, 16h or any two thereof.

[0076] In step 3), the redox medium is pretreated with an inert atmosphere N2, the N2 flow rate is 20 mL / min, the redox medium is vacuum vaporized, the redox medium solution vaporization load is 5L-10L, and a stepwise gradient deposition is performed. The redox medium is first deposited once on the surface of the second intermediate to obtain a third intermediate having a first shell layer.

[0077] In step 4), a secondary deposition is performed on the surface of the third intermediate to obtain a fourth intermediate having a second shell layer.

[0078] In step 5), three depositions are performed on the surface of the fourth intermediate to obtain the above-mentioned positive electrode lithium supplement material.

[0079] In the present application, the redox medium is deposited three times on the surface of the second intermediate to obtain a positive electrode lithium replenishing material with a gradient distribution of fluorine elements provided in the first aspect of the present application, and the structural stability of the positive electrode lithium replenishing material is improved, thereby improving the cycle stability of the battery.

[0080] In some embodiments of the present application, the temperature of the primary deposition is 400-450° C., the deposition rate is 0.01-0.02 μm / min, and the deposition time is 2.5-30 min.

[0081] In some embodiments, the secondary deposition temperature is 350-400° C., the deposition rate is 0.02-0.03 μm / min, and the deposition time is 10-25 min.

[0082] In some embodiments, the temperature of the three depositions is 300-350° C., the deposition rate is 0.03-0.035 μm / min, and the deposition time is 6-28 min.

[0083] Exemplarily, the temperature of a deposition may be 400°C, 410°C, 420°C, 430°C, 440°C, 450°C or a range consisting of any two thereof, the rate of a deposition may be 0.01 μm / min, 0.012 μm / min, 0.015 μm / min, 0.018 μm / min, 0.02 μm / min or a range consisting of any two thereof, and the time of a deposition may be 2.5 min, 5 min, 10 min, 20 min, 30 min or a range consisting of any two thereof. The temperature of the secondary deposition may be 350°C, 360°C, 370°C, 380°C, 390°C, 400°C or a range consisting of any two thereof, the rate of the secondary deposition may be 0.02μm / min, 0.022μm / min, 0.025μm / min, 0.028μm / min, 0.03μm / min or a range consisting of any two thereof, and the time of the secondary deposition may be 10min, 15min, 20min, 22min, 25min or a range consisting of any two thereof. The temperature of the three depositions can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C or a range consisting of any two of them, the rate of the three depositions can be 0.03μm / min, 0.031μm / min, 0.032μm / min, 0.033μm / min, 0.034μm / min, 0.035μm / min or a range consisting of any two of them, and the time of the three depositions can be 6min, 10min, 15min, 20min, 25min, 28min or a range consisting of any two of them.

[0084] The preparation process of the positive electrode lithium replenishment material in this application is simple and the reaction conditions are mild, so the use range of the shell layer can be expanded. Different deposition temperatures and deposition rates can form a shell layer with gradually increasing density along the direction from the positive electrode lithium replenishment matrix material to the shell layer. This gradual transition of density strengthens the binding of the redox medium and the positive electrode lithium replenishment matrix material, which is conducive to improving the charge transfer and ion diffusion process, and effectively enhances the stability of the positive electrode lithium replenishment material, thereby improving the cycle performance of the battery.

[0085] In a third aspect, the present application provides a positive electrode sheet, comprising the positive electrode lithium replenishing material of the first aspect and the positive electrode lithium replenishing material prepared by the preparation method of the second aspect.

[0086] In some embodiments of the present application, Figure 4 As shown, the positive electrode sheet includes a positive electrode current collector, a positive electrode active material layer existing on the surface of the positive electrode current collector, and a positive electrode lithium replenishing layer existing on the side of the positive electrode active material layer away from the positive electrode current collector.

[0087] The positive electrode sheet of the present application can be prepared by a preparation method comprising the following steps:

[0088] 1) applying a positive electrode slurry comprising a positive electrode active material, a conductive agent and a binder to at least one functional surface of a positive electrode current collector to obtain a positive electrode sheet precursor;

[0089] 2) coating a positive electrode lithium replenishing slurry including a positive electrode lithium replenishing material, a conductive agent, and a binder on a side of the positive electrode slurry in the positive electrode sheet precursor away from the positive electrode current collector to obtain the positive electrode sheet.

[0090] The present application does not particularly limit the specific categories of the conductive agent and the adhesive. The conductive agent, the adhesive and other components can be selected from conventional substances in the field. For example, the conductive agent can be selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene, and the adhesive can be selected from one or more of polyvinylidene fluoride (PVDF), acrylic modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber, and styrene-propylene rubber.

[0091] The present application does not specifically limit the coating method, and any coating method such as gravure coating, extrusion coating, spraying, screen printing, etc. can be used to coat the positive electrode active layer slurry.

[0092] Conventional positive electrode lithium replenishing materials are used by slurrying and coating them together with positive electrode active materials. This application adopts a double-layer coating method in which the positive electrode lithium replenishing materials and the positive electrode active materials are slurried separately. This can not only fully utilize the capacity of the positive electrode lithium replenishing materials, but also prevent the conductive network of the positive electrode slurry from being destroyed, thereby ensuring the stability of lithium ion dynamics, while ensuring the adhesion between the collector and the current collector, avoiding electrical isolation, and ensuring the normal transport of electrons.

[0093] In a fourth aspect, the present application provides a battery, comprising the positive electrode sheet of the third aspect.

[0094] The battery of the present application includes a separator, a negative electrode and an electrolyte in addition to a positive electrode sheet. The composition of the negative electrode sheet can refer to conventional negative electrode sheets in the art, and the separator can also be a separator conventionally used in the art, such as a PP film, a PE film, etc.

[0095] The battery of the present application can be prepared by conventional methods in the art. Specifically, the positive electrode sheet, the separator and the negative electrode sheet can be stacked in sequence, and the battery cell can be obtained through a stacking or winding process, and then through baking, liquid injection, formation, packaging and other processes to obtain the above-mentioned battery.

[0096] The technical solution of the present application is further explained below in conjunction with specific embodiments.

[0097] Example 1

[0098] The method for preparing the positive electrode sheet of this embodiment comprises the following steps:

[0099] 1) Lithium hydroxide and oxalic acid containing the C element were placed in a high-speed mixer at a mass ratio of 1.2:1 and mixed for 5 hours until uniformly mixed to obtain sample A1.

[0100] 2) placing sample A1 in a ball mill and grinding it at 500 rpm to obtain sample A2;

[0101] 3) Sample A2 was sintered once in an inert gas N2 atmosphere at a sintering temperature of 500°C and a holding time of 8 hours to obtain a first intermediate.

[0102] 4) The first intermediate is cooled and then ball-milled again, and the crushed first intermediate is sintered for the second time in an inert gas N2 atmosphere at a sintering temperature of 800°C and a holding time of 10 hours to obtain a second intermediate.

[0103] 5) The redox medium K2ZrF6 was pretreated with an inert atmosphere N2, the N2 flow rate was 20 mL / min, the redox medium was vacuum vaporized, the redox medium solution vaporization load was 6 L, and segmented gradient deposition was performed. The first deposition temperature was 450°C, the deposition rate was 0.02 μm / min, and the deposition time was 15 min; the second deposition temperature was 400°C, the deposition rate was 0.03 μm / min, and the deposition time was 16 min; the third deposition temperature was 350°C, the deposition rate was 0.035 μm / min, and the deposition time was 28 min. After the third deposition, the positive electrode lithium supplement material was obtained.

[0104] Among them, the chemical formula of the positive electrode lithium supplement matrix material is Li2C2O4, the D50 of the positive electrode lithium supplement matrix material is 9.65μm, the chemical formula of the shell layer existing on the surface of the positive electrode lithium supplement matrix material is K2ZrF6, and the total thickness d of the shell layer is 1.8μm. The thickness of the first shell layer existing on the surface of the positive electrode lithium supplement matrix material is 0.3μm, and the mass percentage of the fluorine element in the first shell layer to the positive electrode lithium supplement material is 1%, which is recorded as ratio 1; the thickness of the second shell layer existing on the side of the first shell layer away from the positive electrode lithium supplement matrix material is 0.5μm, and the mass percentage of the fluorine element in the second shell layer to the positive electrode lithium supplement material is 2.5%, which is recorded as ratio 2; the thickness of the third shell layer existing on the side of the second shell layer away from the positive electrode lithium supplement matrix material is 1μm, and the mass percentage of the fluorine element in the third shell layer to the positive electrode lithium supplement material is 4%, which is recorded as ratio 3. After X-ray diffraction analysis, the half-peak width FWHM (003) of the diffraction peak corresponding to the (003) crystal plane in the X-ray diffraction pattern of the positive electrode lithium supplement material is 0.214°; where FWHM (003) = 0.0027d 2 +0.13d+0.13, d is the total thickness of the shell layer. The ratio of the area of ​​the positive electrode lithium supplementing matrix material surface without the shell layer to the total area of ​​the positive electrode lithium supplementing matrix material surface is 5%, which is recorded as ratio 4.

[0105] 6) At 25°C and normal pressure (0.1MPa), the positive electrode active material NCM622, the conductive carbon black Super P, and the binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in an N-methylpyrrolidone solvent at a mass ratio of 8:1:1 to obtain a positive electrode slurry with a solid content of 70%. The positive electrode lithium replenishing material, conductive carbon black, and binder polyvinylidene fluoride (PVDF) in step 5) are fully stirred and mixed in an N-methylpyrrolidone solvent at a mass ratio of 4:2:2 to obtain a positive electrode lithium replenishing slurry with a solid content of 20%. The positive electrode lithium replenishing slurry is applied to the current collector Al foil by transfer coating, and the positive electrode slurry loading surface density is controlled to 15mg / cm 2 , the coating speed is 1mL / min. After the positive electrode slurry is pre-coated for 400mm, the slurry nozzle is turned on to spray the positive electrode lithium supplement slurry, the spraying pressure is 0.5MPa, and the spraying speed is 10mL / min. The coated positive electrode sheet is dried in an oven at 110℃ to obtain a positive electrode sheet. Figure 4 As shown, the positive electrode sheet includes a positive electrode current collector, a positive electrode active material layer present on the surface of the positive electrode current collector, and a positive electrode lithium replenishing layer present on the side of the positive electrode active material layer away from the positive electrode current collector.

[0106] Example 2

[0107] The preparation methods of the positive electrode sheets of Example 2 and Example 1 are basically the same, except that the primary sintering temperature in step 5) is changed to 300°C.

[0108] Example 3

[0109] The preparation method of the positive electrode sheet of Example 3 is basically the same as that of Example 1, except that the sintering time in step 5) is changed to 16 hours.

[0110] Example 4

[0111] The preparation method of the positive electrode sheet of Example 4 is basically the same as that of Example 1, except that the secondary sintering temperature in step 5) is changed to 600°C.

[0112] Example 5

[0113] The preparation method of the positive electrode sheet of Example 5 is basically the same as that of Example 1, except that the secondary sintering time in step 5) is changed to 16 hours.

[0114] Example 6

[0115] The preparation method of the positive electrode sheet of Example 6 is basically the same as that of Example 1, except that in step 6), the positive electrode slurry and the positive electrode lithium supplement slurry are mixed evenly in a mass ratio of 8:2, and transfer coating is adopted, and the load surface density is controlled to 15 mg / cm 2 The coating speed is 1 mL / min. The obtained positive electrode sheet includes a positive electrode active material layer, and the positive electrode lithium supplement material exists in the positive electrode active material layer.

[0116] Example 7-25

[0117] The preparation methods of the positive electrode sheets of Examples 7-25 and Example 1 are basically the same, except that one or more of the preparation conditions are changed.

[0118] Comparative Example 1

[0119] The preparation methods of the positive electrode sheets of Comparative Example 1 and Example 1 are basically the same, except that the three deposition treatments in step 5) are not performed, and the chemical formula of the obtained positive electrode lithium supplement material is Li2C2O4.

[0120] Comparative Example 2

[0121] The preparation methods of the positive electrode sheets of Comparative Example 2 and Example 5 are basically the same, except that the three deposition treatments in step 5) are not performed, and the chemical formula of the obtained positive electrode lithium supplement material is Li2C2O4.

[0122] Comparative Example 3

[0123] The preparation method of the positive electrode sheet of Comparative Example 3 is basically the same as that of Example 1, except that in step 5), the first deposition temperature is 350°C, and the deposition rate is 0.035 μm / min; the second deposition temperature is 400°C, and the deposition rate is 0.03 μm / min; the third deposition temperature is 450°C, and the deposition rate is 0.02 μm / min. After the three depositions, the positive electrode lithium supplement material is obtained.

[0124] Comparative Example 4

[0125] The preparation method of the positive electrode sheet of Comparative Example 4 is basically the same as that of Example 1, except that the first deposition temperature in step 5) is 450°C, the deposition rate is 0.02 μm / min, the deposition time is 90 min, and the second and third depositions are not performed.

[0126] Comparative Example 5

[0127] The preparation method of the positive electrode sheet of Comparative Example 5 is basically the same as that of Example 1, except that the first deposition temperature in step 5) is 400°C, the deposition rate is 0.03 μm / min, the deposition time is 60 min, and the second and third depositions are not performed.

[0128] Comparative Example 6

[0129] The preparation method of the positive electrode sheet of Comparative Example 6 is basically the same as that of Example 1, except that the first deposition temperature in step 5) is 350°C, the deposition rate is 0.035 μm / min, the deposition time is 51 min, and the second and third depositions are not performed.

[0130] Test example:

[0131] 1. Fluorine content: The fluorine content is measured by linear scanning from the center of the sphere to the outside using an energy dispersive spectrometer (EDS).

[0132] 2. Shell thickness: The shell thickness is measured by linear scanning from the center of the body to the outside using an energy dispersive spectrometer (EDS). Specifically, after depositing the first shell layer on the positive electrode lithium supplementation matrix material, an EDS line scan is performed, and the thickness of the first shell layer is obtained by testing the thickness of the area where the mass percentage of the fluorine element is greater than 0.5%; after depositing the second shell layer on the positive electrode lithium supplementation matrix material, an EDS line scan is performed, and the first thickness is obtained by testing the thickness of the area where the mass percentage of the fluorine element is greater than 1.5%, and the second shell thickness is obtained by subtracting the first shell thickness from the first thickness; after depositing the third shell layer on the positive electrode lithium supplementation matrix material, an EDS line scan is performed, and the second thickness is obtained by testing the thickness of the area where the mass percentage of the fluorine element is greater than 3%, and the third shell thickness is obtained by subtracting the first thickness from the second thickness.

[0133] 3. D50: Use laser particle size analyzer to test the particle size of the material.

[0134] 4. The half-peak width FWHM(003) of the diffraction peak corresponding to the (003) crystal plane in the XRD pattern: The XRD pattern of the material tested by X-ray diffraction is used to derive the half-peak width FWHM(003) of the diffraction peak corresponding to the (003) crystal plane.

[0135] 5. The ratio of the surface area of ​​the positive electrode lithium-replenishing matrix material without the shell layer to the total surface area of ​​the positive electrode lithium-replenishing matrix material: Use SEM particle statistical analysis software to count all identified particles according to the gray value to obtain the surface coating ratio. Set the total area to 100%, then the uncoated ratio is 100% minus the surface coating ratio.

[0136] 6. Phase transition peak position: The phase transition peak positions I1 and I2 are obtained by the differential capacitance (dQ / dV) curve derived from the prepared battery cycle test.

[0137] 7. Impedance: The impedance of the prepared battery is tested using a Princeton impedance tester to obtain the impedance value.

[0138] 8. Cycle performance: The positive electrode sheet in each embodiment and comparative example is used, the negative electrode is graphite, and the separator is polypropylene, and the electrolyte (composition is 1 mol / L LiPF6, the solvent is EC / DMC / DEC=v / v / v:1 / 1 / 1) is used to form a full battery. At 25°C, it is charged to 4.35V at a constant current of 1C, and then charged to a current rate of 0.5C at 4.35V. Then, it is discharged to 3V at a discharge rate of 1C. This charge and discharge cycle is repeated 300 times, and the discharge capacity Q1 at the first cycle and the discharge capacity Q at the 300th cycle are measured. 300 The capacity retention rate after 300 cycles is Q = Q 300 / Q1*100%.

[0139] Figure 1 This is a cross-sectional SEM image of the positive electrode lithium replenishing material prepared in Example 1 of the present application.

[0140] from Figure 1 It can be seen that the content of fluorine in the positive electrode lithium supplement material prepared in Example 1 of the present application is distributed in a gradient.

[0141] Figure 2 This is a surface SEM image of the positive electrode lithium replenishing material prepared in Example 1 of the present application.

[0142] from Figure 2 It can be seen that there is a uniformly coated shell layer on the surface of the positive electrode lithium supplement material prepared in Example 1 of the present application.

[0143] Figure 3 This is a graph showing the change in the fluorine content in the positive electrode lithium replenishing material prepared in Example 1 of the present application along the distance from the positive electrode lithium replenishing matrix material to the shell layer.

[0144] from Figure 3 It can be seen that the content of fluorine in the positive electrode lithium replenishing material prepared in Example 1 of the present application tends to increase along the direction from the positive electrode lithium replenishing matrix material to the shell layer.

[0145] Table 1

[0146]

[0147]

[0148] Table 2

[0149]

[0150]

[0151] From Table 1-2, it can be seen that compared with the comparative example, the positive electrode lithium replenishing material of the present application can replenish lithium for the battery and make up for the loss of lithium ion concentration caused by the lithium ion battery during the cycle process, and the fluorine content in the shell layer of the positive electrode lithium replenishing material in the present application tends to increase along the direction from the positive electrode lithium replenishing matrix material to the shell layer, and a shell layer with gradually increasing density can be formed, which effectively enhances the structural stability of the positive electrode lithium replenishing material, and thus improves the cycle stability of the battery.

[0152] From the comparison between Example 1 and Comparative Example 1, it can be seen that the positive electrode lithium replenishing material without a shell layer has poor structural stability and fails to effectively activate dead lithium during the cycle process.

[0153] From the comparison between Example 1 and Comparative Example 2, it can be seen that the positive electrode lithium replenishing material without a shell layer is mixed with the positive electrode slurry, the slurry coating cycle stability is poor, and the positive electrode lithium replenishing material fails to play a role.

[0154] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A positive electrode lithium supplement material, characterized in that: It comprises a positive electrode lithium-replenishing matrix material and a shell layer existing on at least part of the surface of the positive electrode lithium-replenishing matrix material; the shell layer comprises fluorine element, and the content of fluorine element in the shell layer increases along the direction from the positive electrode lithium-replenishing matrix material to the shell layer.

2. The positive electrode lithium supplement material according to claim 1, characterized in that: The chemical formula of the shell is A a ZF b , wherein 0<a≤2, 4≤b≤6, A is selected from at least one of K, Na, and NH4; And / or, the chemical formula of the positive electrode lithium supplement matrix material is Li x M y O z , wherein 0<x≤4, 0<y≤2, 0<z≤4, and M is selected from at least one of C, Ni, Co, Mn, and Fe.

3. The positive electrode lithium supplement material according to claim 1 or 2, characterized in that: The shell layer includes a first shell layer existing on the surface of the positive electrode lithium supplement matrix material, a second shell layer existing on a side of the first shell layer away from the positive electrode lithium supplement matrix material, and a third shell layer existing on a side of the second shell layer away from the positive electrode lithium supplement matrix material; The content of fluorine in the first shell layer is less than that in the second shell layer, and the content of fluorine in the second shell layer is less than that in the third shell layer.

4. The positive electrode lithium supplement material according to claim 3, characterized in that: The thickness of the first shell layer is 0.05 μm-0.6 μm; the thickness of the second shell layer is 0.3 μm-0.75 μm; the thickness of the third shell layer is 0.2 μm-1 μm; And / or, the mass percentage of fluorine element in the first shell layer to the positive electrode lithium replenishing material is 0.01%-1.5%; the mass percentage of fluorine element in the second shell layer to the positive electrode lithium replenishing material is 1%-3%; the mass percentage of fluorine element in the third shell layer to the positive electrode lithium replenishing material is 3%-5%.

5. The positive electrode lithium supplement material according to any one of claims 1 to 4, characterized in that: The D50 of the positive electrode lithium supplement matrix material is 8 μm-10 μm; the total thickness d of the shell layer is 1 μm-2.1 μm; And / or, after X-ray diffraction analysis, the half-peak width FWHM (003) of the diffraction peak corresponding to the (003) crystal plane in the X-ray diffraction pattern of the positive electrode lithium supplement material is 0.25°-0.42°; wherein, FWHM (003) = 0.0027d 2 +0.13d+0.13, d is the total thickness of the shell; And / or, the proportion of the area of ​​the portion of the surface of the positive electrode lithium-replenishing matrix material where the shell layer does not exist to the total surface area of ​​the positive electrode lithium-replenishing matrix material is less than or equal to 5%.

6. The positive electrode lithium supplement material according to any one of claims 1 to 5, characterized in that: In the differential capacitance curve of the battery cycle 0-200 cycles prepared by the positive electrode lithium supplement material, in the range of 4.1V-4.3V, the fluctuation range of the phase transition peak position I1 is 0%-2%; in the range of 3.4V-3.7V, the fluctuation range of the phase transition peak position I2 is 0%-5%.

7. A method for preparing a positive electrode lithium supplement material according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) sintering the raw material system including the lithium source and the M source at 300° C.-500° C. in an inert gas atmosphere for 8 h-16 h to obtain a first intermediate; 2) performing secondary sintering on the first intermediate at 600° C.-800° C. in an inert gas atmosphere for 8 h-16 h to obtain a second intermediate; 3) allowing a redox medium to be deposited once on the surface of the second intermediate to obtain a third intermediate; 4) allowing the redox mediator to be deposited secondary on the surface of the third intermediate to obtain a fourth intermediate; 5) allowing the redox medium to be deposited three times on the surface of the fourth intermediate to obtain the positive electrode lithium supplement material.

8. The preparation method according to claim 7, characterized in that: The temperature of the primary deposition is 400-450° C., the deposition rate is 0.01-0.02 μm / min, and the deposition time is 2.5-30 min. And / or, the secondary deposition temperature is 350-400° C., the deposition rate is 0.02-0.03 μm / min, and the deposition time is 10-25 min; And / or, the temperature of the three depositions is 300-350° C., the deposition rate is 0.03-0.035 μm / min, and the deposition time is 6-28 min.

9. A positive electrode sheet, characterized in that: The invention comprises the positive electrode lithium replenishing material according to any one of claims 1 to 6, and the positive electrode lithium replenishing material prepared by the preparation method according to claim 7 or 8.

10. The positive electrode sheet according to claim 9, characterized in that: The positive electrode sheet includes a positive electrode current collector, a positive electrode active material layer existing on the surface of the positive electrode current collector, and a positive electrode lithium supplement layer existing on a side of the positive electrode active material layer away from the positive electrode current collector.

11. A battery, characterized in that: Including the positive electrode sheet as described in claim 9 or 10.

Citation Information

Patent Citations

  • Lithium supplement additive and preparation method and application thereof

    CN115312770A

  • Lithium supplement material and preparation method thereof, positive pole piece and secondary battery

    CN116314713A

  • Positive electrode lithium supplementing material and preparation method thereof, positive electrode plate and secondary battery

    CN117334908A

  • Lithium supplement material and preparation method thereof, positive electrode material and secondary battery

    CN117525423A

  • Positive electrode lithium supplementing material and preparation method and application thereof

    CN117712327A